Analisis Kandungan Rhodamin B pada Saus Sambal dengan Metode Tes Kit di Depan Kampus Universitas Halu Oleo Tahun 2025 - Anggun Saputri Gane; Hartati Bahar; Jumakil Jumakil (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Rhodamine B is one of the synthetic dyes commonly used as a dye for paper, textiles or ink. This study aims to analyze the presence of Rhodamine B food coloring in chili sauce in front of the Halu Oleo University campus in 2025. The method used in this study is descriptive qualitative with laboratory testing using the test kit method. The population in this study was 10 types of chili sauce, which were taken from each restaurant or used in snacks in front of the Halu Oleo University Campus, Kendari City. The sample was determined using the total sampling method with a total sample of 10 samples. The results of this study indicate that 10 samples of chili sauce used in restaurants and snack vendors circulating in front of the Halu Oleo University campus were declared not to contain Rhodamine-B.